Long-Term Effects of COVID-19 and the Pandemic on Tinnitus Patients - Erinc, Murat; Mutlu, Ahmet; Celik, Serdal; Kalcioglu, Mahmut Tayyar; Szczepek, Agnieszka J. (Frontiers in Neurology, 2022)
This study aimed to explore the effect of COVID-19 and the pandemic period on the tinnitus-related complaints of patients with chronic tinnitus. Ninety-six patients who were diagnosed with chronic tinnitus before the pandemic were enrolled in this study. Before the pandemic and in January 2022, all patients used the Visual Analog Scale (VAS) to assess tinnitus loudness, annoyance, and effect on everyday life, sleep, and concentration. Additionally, patients filled the Tinnitus Handicap Inventory (THI) and the Hyperacusis Questionnaire (HQ). In the entire cohort, tinnitus loudness, annoyance, and tinnitus-induced difficulties with concentration as well as THI and HQ scores increased significantly during the two pandemic years. Thirty-seven tinnitus patients contracted COVID-19 between March 2020 and January 2022. These patients were asked to list leading COVID-19 symptoms, changes in tinnitus complaints during and after the disease, and whether their hearing abilities were affected. Three patients in the COVID-19 group confirmed worsening their hearing abilities. There was no decrease in the tinnitus complaint during COVID-19, 24.3% of the infected patients reported exacerbation of tinnitus, and 75.7% said tinnitus remained the same. In the COVID-19-negative group, 13.5% reported tinnitus decrease during the pandemic, 57.6% said it remained the same, and 28.8% reported exacerbation of tinnitus. When split into infected and non-infected groups, a significant increase in tinnitus loudness, tinnitus effect on concentration, and THI scores were seen only in patients who contracted COVID-19, while hyperacusis worsened significantly (p < 0.05) only in COVID-19-negative tinnitus patients. Despite significant differences within the groups, there were no differences found between the groups. This study points to possible different effects of the infection with SARS-CoV-2 and the pandemic period on patients with chronic tinnitus. It also provides evidence for deterioration of preexisting tinnitus as a possible long-term effect of COVID-19.